Analisis Produktivitas Tenaga Kerja Industri Gamelan Di Desa Tihingan Kabupaten Klungkung - Adiati, Nyoman Ayu; Mustika, Made Dwi Setyadhi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 2, No. 5, Mei 2013 (pp. 226-276), 2013)
The economic sector in Bali increased by the influence of the industrial sector, whereas Gamelan is one of the successful industry in Tihingan village in regency Klungkung.Wage, work experience and technology are the key influence of increscent productivity of Gamelan industry in Tihingan village. This research aims is to understand the influence of wage, work experience and technology by simultan and partial and to understand regarding the dominant variable that influence the productivity of workers for Gamelan industry. This research was conduct in tihingan village with samples of 66 participants. Technic of this research used multiple linear regression. Results of this research shows that wagess, work experience and technology are significantly influencing to the productivity coefficients of determination (R 2 ) 0,649. Partically, wage and technology are the positive influence of the productivity, while the work experience has no effect partially. Wage are the dominant variables influencing the productivity of workers.
Keywords: wage , work experience , technology , productivity